2007
DOI: 10.1007/s00477-007-0104-7
|View full text |Cite
|
Sign up to set email alerts
|

Inter-station correlation and estimation errors of areal average rain rate

Abstract: In this study an equation for estimating the error involved in the areal average rain rate considering the inter-station correlation was derived and applied for two cases: the first compared two storm events with different inter-station correlations, and the second evaluated the seasonal variation of estimation error of monthly rainfall. Similar cases, but without considering the rainfall seasonality, were also investigated for the comparison. This study was applied to the Geum River Basin with 28 rain gauge m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…Salah satu cara untuk merepresentasikan kondisi hidrologi DAS secara spasial adalah melakukan analisis hujan rerata wilayah. Metode yang sering dimanfaatkan dalam analisis hujan wilayah adalah Metode Rerata Aritmatik, Isohyet dan Thiessen (Yoo , et al, 2008). Metode rerata aritmatik, Thiessen dan Isohyet merupakan metode analisis hujan wilayah yang menitepretasikan faktor kuantitas fisik alat ukur hujan dalam skala geometris (Ribeiro, et al, 2021).…”
Section: Latar Belakangunclassified
See 1 more Smart Citation
“…Salah satu cara untuk merepresentasikan kondisi hidrologi DAS secara spasial adalah melakukan analisis hujan rerata wilayah. Metode yang sering dimanfaatkan dalam analisis hujan wilayah adalah Metode Rerata Aritmatik, Isohyet dan Thiessen (Yoo , et al, 2008). Metode rerata aritmatik, Thiessen dan Isohyet merupakan metode analisis hujan wilayah yang menitepretasikan faktor kuantitas fisik alat ukur hujan dalam skala geometris (Ribeiro, et al, 2021).…”
Section: Latar Belakangunclassified
“…Kondisi kerapatan stasiun hujan dan sebaran distribusi hujan di DKI Jakarta maupun di kawasan penyangga Jakarta menyebabkan hujan wilayah dengan metode rerata aritmatik tidak dapat digunakan, karena deviasi antar stasion hujan lebih dari 10% sementara kriteria pemanfaatan hujan rerata aritmatik adalah deviasi antar stasion hujan kurang dari 10% (Yoo , et al, 2008). Terjadinya serangkaian banjir yang semakin sering terjadi dan terulang tiap tahun, menuntut upaya lebih besar mengantisipasinya, sehingga kerugian dapat diminimalkan.…”
Section: Latar Belakangunclassified
“…The arithmetic average method assumes that the rainfall field is homogeneous and that the rain gauge observations are independent; thus, it gives equal weight to all rain gauges [1,6]. The Thiessen polygon technique sets a fixed weighting factor for the areal coverage of a station.…”
Section: Introductionmentioning
confidence: 99%
“…Kriging methods (e.g., ordinary kriging, universal kriging, and cokriging) are known as geostatistical approaches or multivariate geostatistical techniques with spatial correlation patterns [6,[8][9][10][11]. Previous case studies have confirmed their effectiveness in the spatial interpolation of rainfall within mountainous terrain [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%